Occurrence of Microplastic Pollution in the Beibu Gulf, the Northern South China Sea - Zhu, Zuhao; Wei, Huihua; Huang, Wei; Wu, Xingxu; Guan, Yao; Zhang, Qiufeng (Frontiers in Marine Science, 2022)
In this study, microplastics were sampled and analyzed from surface water and sediment samples from July to August in 2020, in the Beibu Gulf (the northern South China Sea [SCS]), a gulf with intensive fishery activities while the economy is less developed, compared with other coastal areas of China. The abundances of microplastics in seawater and sediment in the Beibu Gulf were 0.67 items/m3 and 4.33 items/kg of dry weight, respectively. In seawater, the fragments (92.38%) contributed the most, and polystyrene (PS) was the dominant polymer (53.23%). In sediment, the most abundant microplastics were fiber (82.93%) and rayon (RY; 39.54%). The abundances of remarkably higher microplastics were found in the seawater and sediment adjacent to the urban area. The abundances of microplastics in far coastal sediment were only slightly lower than that in the coastal sediment, indicating that microplastics are ready to transport and bury in open area sediment. Significant positive correlations between the microplastic abundance and population density and per capita gross domestic product (GDP) were found in Chinese coastal seawater, with low population density and less developed economy, and the microplastic pollution in the Beibu Gulf was at a low level. This study provides preliminary data of microplastics in the Beibu Gulf, supporting further investigation of transportation fate and management of this emerging pollutant from the coastal zone to the SCS.